2007
DOI: 10.1016/j.apm.2006.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis and modeling of structure with bolted joints

Abstract: In this work, in order to investigate a modeling technique of the structure with bolted joints, four kinds of finite element models are introduced; a solid bolt model, a coupled bolt model, a spider bolt model, and a no-bolt model. All the proposed models take into account pretension effect and contact behavior between flanges to be joined. Among these models, the solid bolt model, which is modeled by using 3D solid elements and surface-to-surface contact elements between head/ nut and the flange interfaces, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
166
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(168 citation statements)
references
References 10 publications
1
166
0
1
Order By: Relevance
“…Some reports have found that nonlinear features like frictional contact elements cannot be counted in a modal analysis [3,16], and this has caused other research to employ linear contact for the modal analysis. In this study, the effects of the frictional contact are taken into account in dynamic analysis as pre-stressed modal analysis, in which the static structural analysis with contact element results in the stress and elastic strain which are maintained as initial condition of next analysis, modal analysis.…”
Section: Frequency Response Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports have found that nonlinear features like frictional contact elements cannot be counted in a modal analysis [3,16], and this has caused other research to employ linear contact for the modal analysis. In this study, the effects of the frictional contact are taken into account in dynamic analysis as pre-stressed modal analysis, in which the static structural analysis with contact element results in the stress and elastic strain which are maintained as initial condition of next analysis, modal analysis.…”
Section: Frequency Response Analysismentioning
confidence: 99%
“…Kim proposed four kinds of finite element models to model structures with bolted joints [3]. Ahmadian developed a nonlinear generic element formulation for modeling bolted lap joints [4].…”
Section: Introductionmentioning
confidence: 99%
“…Proper modelling of bolted joints is critical to estimating the dynamic characteristics of reciprocating compressors. The characteristics of bolted joints have drawn much attention in recent years [5][6][7][8][9][10][11][12]. Pratt and Pardoen [5] proposed nonlinear finite element models to predict the load-elongation behaviour of conical-head bolted lap joints and verified simulation results by the comparison to test data.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [6] compared the calculation accuracy and efficiency of four kinds of bolt finite element models. Ref.…”
Section: Introductionmentioning
confidence: 99%